2020
DOI: 10.1101/2020.07.22.216523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental DNA metabarcoding provides enhanced detection of the European eelAnguilla anguillaand fish community structure in pumped river catchments

Abstract: The European eel Anguilla anguilla (eel hereafter) is critically endangered and has a catadromous lifecycle, which means adult eels that live in pumped catchments must pass through pumps during their downstream spawning migration. We are currently lacking detailed site-by-site eel distribution information in order to estimate the overall impact of individual pumping stations on eel escapement, and as such lack the data to enable informed prioritisation of pumping station management and targeted mitigation. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…More detailed quantitative data on fish abundance in the environment are required to distinguish prey selection from density-dependent predation. Indeed, small and benthic species are often underreported in conventional fish surveys, but recent eDNA metabarcoding studies have shown that these species might be much more abundant than previously thought (Hänfling et al 2016; Li et al 2019; Griffiths et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More detailed quantitative data on fish abundance in the environment are required to distinguish prey selection from density-dependent predation. Indeed, small and benthic species are often underreported in conventional fish surveys, but recent eDNA metabarcoding studies have shown that these species might be much more abundant than previously thought (Hänfling et al 2016; Li et al 2019; Griffiths et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…All downstream analyses were carried out using R version 3.6.3 (R Core Team, 2019). A low-frequency read threshold of 0.001 was applied to eDNA data, removing any reads which make up less than 0.1% of total reads assigned to any given sample as previously applied in other studies using this 12S marker (Griffiths et al, 2020; Handley et al, 2019; Hänfling et al, 2016). All maps were visualised, and associated metadata extracted using QGIS (QGIS Development Team, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the eel distribution in Cyprus, and therefore inform current status, a wide range of catchments must be monitored in a short time frame. Environmental DNA (eDNA) metabarcoding of water samples has already proven to be effective for monitoring A. anguilla in heavily modified river systems in the UK (Griffiths et al, 2020). Therefore, this case study builds upon current knowledge by applying eDNA metabarcoding of water samples taken in 2020, alongside data from electrofishing/netting surveys carried out over a ten-year period (2009 - 2019) as part of the national WFD monitoring programme.…”
Section: Introductionmentioning
confidence: 99%
“…In the primary reaction the metabarcoding primers carry 5′ sequence overhangs of c. 33–34 nucleotides in length. These can be with (Clarke et al, 2017; Griffiths et al, 2020; Kitson et al, 2018; Li et al, 2019; Vesterinen et al, 2018) or without (Bista et al, 2017; de Vere et al, 2017; Galan et al, 2017; Miya et al, 2015; Swift et al, 2018; Vesterinen et al, 2018) nucleotide tags (Figure 2c,d). The sequence overhangs allow the resulting amplicons to be targeted by the second round of primers, which carry sequencing adapters and indices.…”
Section: Tagging and Indexing Approaches In Metabarcoding Studiesmentioning
confidence: 99%